A Magnetic Resonance Imaging–Based Staging System for Osteochondritis Dissecans of the Elbow: A Validation Study Against the International Cartilage Repair Society Classification. Issue 9 (5th September 2018) - Kohyama, Sho; Ogawa, Takeshi; Mamizuka, Naotaka; Hara, Yuki; Yamazaki, Masashi
Background: Evaluations of the stability of osteochondritis dissecans (OCD) lesions of the elbow using magnetic resonance imaging (MRI) have resulted in reports with variable accuracy. Therefore, the International Cartilage Repair Society (ICRS) classification remains the gold standard to determine OCD lesion stability. Because OCD commonly occurs in pediatric patients, a noninvasive method comparable with the ICRS classification is desired. Hypothesis/Purpose: Based on the previous literature, the capitellum of unstable OCD lesions has an irregular outline on MRI because of displacement or dislocation of the lesion via synovial fluid inflow. Therefore, we defined a 4-stage classification, similar to the ICRS classification, which focused on the outline of the capitellum and articular cartilage status on MRI without subchondral bone information. The purpose of this study was to validate this MRI-based staging system against the ICRS classification and to verify its accuracy in diagnosing unstable OCD lesions of the elbow. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: A total of 81 patients with OCD of the elbow who were surgically treated were evaluated. The MRI-based stages were as follows: stage 1, normal-shaped capitellum and articular cartilage without signal intensity change; stage 2, normal-shaped capitellum and articular cartilage with signal intensity change; stage 3, irregular-shaped capitellum and discontinuity of the articular cartilage; and stage 4, dislocated lesion with an articular cartilage defect. Agreement between the MRI and ICRS classifications was evaluated, and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for lesion instability were determined. The intraclass correlation coefficient (ICC) for intrarater and interrater reliability of the MRI-based staging system was calculated. Results: Agreement between the MRI-based staging system and the ICRS classification was 88.9%, with a sensitivity of 98.4%, specificity of 84.2%, PPV of 95.3%, and NPV of 94.1% for diagnosing an unstable lesion. The ICC was high for both intrarater (0.925) and interrater (0.915-0.939) reliability. Conclusion: The MRI-based staging system corresponded well with the ICRS classification, providing an accurate preoperative assessment of OCD lesions of the elbow, even with minimal subchondral bone information.